Signaling High Quality Papers in Angewandte Chemie International Edition and Its Effect on Citation Impact: A Propensity Score Matching Analysis of the Designation ‘Very Important Paper’ (VIP) - Mutz, Rüdiger; Wolbring, Tobias; Daniel, Hans-Dieter; et al. (Journal of the Association for Information Science and Technology, 2016)
Scientific journals publish an increasing number of articles every year. To steer readers’ attention to the most important papers, journals use several techniques (e.g., lead paper). Angewandte Chemie International Edition (AC), a leading international journal in chemistry, signals high-quality papers through designating them as a “very important paper” (VIP). This study aims to investigate the citation impact of Communications in AC receiving the special feature VIP, both cumulated and over time. Using propensity score matching, treatment group (VIP) and control group (non-VIP) were balanced for 14 covariates to estimate the unconfounded “average treatment effect on the treated” for the VIP designation. Out of N = 3,011 Communications published in 2007 and 2008, N = 207 received the special feature VIP. For each Communication, data were collected from AC (e.g., referees’ ratings) and from the databases Chemical Abstracts (e.g., sections) and the Web of Science (e.g., citations). The estimated unconfounded average treatment effect on the treated (that is, Communications designated as a VIP) was statistically significant and amounted to 19.83 citations. In addition, the special feature VIP fostered the cumulated annual citation growth. For instance, the time until a Communication reached its maximum annual number of citations, was reduce